(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2022)
Tribolium confmusum (Coleoptera: Tenebrionidae) is the most stored pest in the world due to the economic damage it causes to stored grain and its products. The use of traditional pesticides and the emergence of resistance in this pest led to a lack of pest control efficiency, which made it necessary to use other safe and effective alternatives to combat it, including essential oils plant extracts. The purpose of this research was to study the effect of six extracts of essential oils: flax Linum usitatissum, citrus limon Linum usitatissum, thymus Thymus vulgaris, rosemary Rosmarinus officinalis, fenugreeks Trigonella foeneum, and cinnamon Cinnamomum verus on larvae and adults of confused flour beetle T. confusum in vitro. Results showed that there were significant differences between oil treatments at 0.05 level, as the rosemary and cinnamon oils killed larvae and adults by 50.1, 50.6 %. In comparison, the effect of thyme and fenugreek oils was 41.28, 39.5%, followed by flax oil with 29.2%. The effect of lemon oil on the adult and larval stages of this pest had a lower killing rate of 5.28%. Results showed that essential oil extracts used in this study gave larval mortality rate of 8.88% compared to adults of 1.66%, with a direct relationship between the concentration rate and the killing rate, i.e., at concentrations of 10-8 and 10-6, the death rate was 54.22 and 48.78% respectively. But, at concentrations of 10-4 and 10-2 the death rate was 25.96% and 15.11% respectively. Laboratory results obtained revealed the ability of plant essential oil extracts different concentrations act as alternatives that repel and kill larval and adult stages of the confused flour beetle T. confusum.